(untitled) (African Journal of Biomedical Research, 2022)
Maternal obesity is a neglected public health challenge in Nigeria, even though it’s associated with adverse metabolic, pregnancy, postpartum outcomes and future risk of non-communicable diseases. The Ibadan Pregnancy Cohort Study (IbPCS) investigates maternal obesity, lifestyle factors and the associated pregnancy and postpartum outcomes in Ibadan, Nigeria. IbPCS is an ongoing prospective cohort study that enrolled 1745 pregnant women at ≤ 20 weeks gestation at their first antenatal visit from four health facilities in Ibadan. Maternal body mass index (BMI) and lifestyle characteristics (Physical Activity - PA and Dietary Pattern) were assessed during enrollment using the pregnancy physical activity questionnaire and a qualitative food frequency questionnaire. The follow-up of participants was at 24 -28 weeks, third trimester, delivery and the postpartum period. Biomarkers (blood glucose and lipid) were assessed during the Oral Glucose Tolerance Test conducted between 24 – 28 weeks’ gestation after an overnight fast. Baseline characteristics were: age (29.8±5.3 years), BMI (26.2±7.1kg/m2), primigravida (32.4%) , married (94.2%) , and tertiary level education (68.3%). This study will provide the preventive tools and lifestyle modification strategies required to mitigate the adverse effect of maternal obesity on maternal and child health and an epidemic of future cardio-metabolic diseases in Nigeria.